9x+27=6x

Simple and best practice solution for 9x+27=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+27=6x equation:


Simplifying
9x + 27 = 6x

Reorder the terms:
27 + 9x = 6x

Solving
27 + 9x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
27 + 9x + -6x = 6x + -6x

Combine like terms: 9x + -6x = 3x
27 + 3x = 6x + -6x

Combine like terms: 6x + -6x = 0
27 + 3x = 0

Add '-27' to each side of the equation.
27 + -27 + 3x = 0 + -27

Combine like terms: 27 + -27 = 0
0 + 3x = 0 + -27
3x = 0 + -27

Combine like terms: 0 + -27 = -27
3x = -27

Divide each side by '3'.
x = -9

Simplifying
x = -9

See similar equations:

| -64=-8y | | 5(4d+8)=-12 | | 13x-11=12x | | -30=-6(m+3) | | 2(a-2)-5(7a+5)=-6a+2a | | 48x+71=78+44x | | 1-5x=-2-4x | | 5(n-4)=7 | | -12-4y-9=-7 | | x^3-18x^2+108x-351=0 | | 3.4x+7.1=6.4x-7.9 | | (2k-11)=7 | | -0.04x=-5 | | -24-4x=20 | | 26=x+12 | | -7(1-2x)=14x | | x+-11y=45.5 | | -7x-8=-60 | | 8=4c+1 | | 9w=32+w | | -7x-6+9x=-4 | | -8(-1+4p)=-5(6p-1)+1 | | 41x-3+20x=180 | | x+y(-11)=45.5 | | 1x+17+2x=7+x | | -3-(1-7A)= | | 41x+3+20x=180 | | 43+x=59 | | 6(1+3)=-8(-2+5)-4 | | 82x+9=-99+82x | | 40n^3+48n^2+5n+6= | | 6(5-2x)-2x=86 |

Equations solver categories